Contemporary International Treaties Seen From the Principles of Maqasid Ash-Shariah - Nugraha, Amal Teguh (Law and Justice, 2022)
Along with the times, the pattern of human interaction continues to evolve. Finally the human communication penetrates the boundaries of nation and state. The pattern which forms the inevitable urgency produces an International Treaties. However, an international treaty in Islam could be accepted if it is in line with Islamic Law, then it is processed into Maqasid Ash-Shariah. This research includes two important issues, ''Islamic relation and global society" and "the existence of Maqashid principles in contemporary International Treaties". This research is normative juridical legal research. It used a conceptual approach, comparative and statutory. From this discussion, it is concluded that the contemporary international treaties mostly contains Maqasid Asy-sharia principles, even a product of an international agreement can be accepted even though the agreement was not initiated by an Islamic country or Muslims.